Application of a discontinuous permeable adsorptive barrier for aquifer remediation. A comparison with a continuous adsorptive barrier. Issue 48 (20th October 2016) - Santonastaso, G.F.; Bortone, I.; Chianese, S.; Erto, A.; Di Nardo, A.; Di Natale, M.; Musmarra, D.
Abstract: This work presents an innovative configuration of a permeable adsorptive barrier (PAB) for the in situ remediation of benzene-contaminated groundwater in the area of Naples (Italy). A PAB is a type of permeable reactive barrier (PRB) made with adsorbing materials (e.g. activated carbon). This particular PAB is a discontinuous permeable adsorptive barrier (PAB-D), consisting in an array of deep passive adsorptive wells whose hydraulic conductivity is higher than the surrounding soil. The design was based on COMSOL Multi-physics ® simulations, which allow for the description of pollutant transport in groundwater and adsorption onto the barrier by means of a 2D model solved using a finite element approach. Based on a hydrological and geotechnical characterization of the entire polluted aquifer, the design and optimization of PAB-D parameters (location, orientation, number of wells and dimensions) were defined. The influence of hydraulic conductivity and dispersivity on the total number of wells for a complete aquifer remediation was investigated. Finally, a comparison with a continuous barrier (PAB-C), i.e. a wall of adsorptive material, in terms of total adsorbing material needed, is presented.